Manufacturing technology in rehabilitation practice: Implications for its implementation in assistive technology production - de Carvalho Filho, Idinei Francisco Pires [UNESP]; Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika; Paschoarelli, Luis Carlos [UNESP] (Springer Nature, 2020)
This study addressed the participation of rehabilitation professionals in the use of Additive Manufacturing to produce assistive technology devices. A literature review based on articles published in scientific journals indexed in the Scopus database was conducted by searching for papers addressing the use of Additive Manufacturing Technologies in the development of orthotic and prosthetic devices in rehabilitation programs. The 46 articles that met the inclusion criteria were analyzed in terms of the participation of the health professionals in the process of design of orthotic and prosthetic devices. The analysis revealed that in most cases the use of 3D printing technologies in the design of assistive devices do not comprise interdisciplinary teams with active participation of rehabilitation professionals.
Keywords: 3D printing; Assistive technologies; Rehabilitation practice